Efficiency of Islamic Income Allocation and Distribution among MSMEs in Pentol Bakar Pacet, Mojokerto - Tanto Fatkhurrozi; Lilik Rahmawati (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Islamic Allocation Efficiency means that no individual can increase his utility without reducing other uses. Islamic allocation efficiency does not allow increasing personal welfare which can cause the welfare of others to decrease. Income Distribution in Islam refers to the distribution of existing assets, both private and public, to the people who are entitled to receive them. One of the goals to be achieved by distributing Islam is a social goal, meeting the needs of groups in need and enlivening the principle of solidarity in Islamic society so that society can live in prosperity. This research uses descriptive qualitative research. Data collection was obtained from interviews and field observations as well as various reading materials, both journals and books. This research resulted in the MSMEs business actors of Pentol Bakar (Grilled Pentol) Pacet being able to be said to be efficient because the allocation of income received from both employees and bosses without the bosses and employees being harmed was not wronged by the MSMEs business actors of Pentol Bakar Pacet in accordance with the theory of income distribution in Islam because there was no efforts to improve the welfare of others over the suffering of others because the income received by employees is greater than what the staff earns. There is also an aspect of justice because in this case no one is harmed by this system, it’s just that employees must continue to optimize their work in order to earn more income. MSMEs actors of Pentol Bakar Pacet are in accordance with Islamic allocation efficiency.